STUDI TENTANG PELAMINAN DIKECAMATAN KOTA BARU KOTA JAMBI - Maydayusi, Dastaty; Yasnidawati, Yasnidawati; Andriani, Adriani (Journal of Home Economics and Tourism, 2015)
This study aimed to describe the aisle Jambi which includes the name of the aisle section, colors, motifs and embroidery techniques, installation techniques, meaning the aisle and Innovation at the altar. This research is descriptive qualitative. Selection techniques informants in this study using snowball sampling technique. Data collection techniques using observation, interviews and documentation. Results of the study revealed that the results of the study revealed that: 1) parts of the aisle that the level ladder, pole, roof, tawing, waves, tongues, egg flower, yellow umbrella, fruit butun, kampek and tenggalung fence. 2) yellow wedding colors, red, black and green. 3) motif used dihiasin using natural motifs with gold thread embroidery technique. 4) installation techniques aisle to aisle include installing decorative frame. a5) the meaning of the parts of this altar symbolizes one's social status. 6) Innovation happens at the altar of Jambi that was formerly attached one now been installed three which left his right to sit where both parents of the bride.Kata Kunci: Pelaminan, Jambi.